Effect of selected shading devices on office room temperature - Whaad, A.M.; Adam, N.M.; Sapuan, S.M.; Saidur, Rahman (International Journal of Mechanical and Materials Engineering, 2010)
This study investigated the effects of selected shading devices on office room temperature. The experimental results were presented to show the thermal effects of coating systems used. Initial work for a duration of two months showed that high temperatures occurred during 10:00, 12:00 and 14:00 hours. The coating materials used, were plain glass pane with the thickness of 5 mm (control), tinted film, silver film, and blinds. Results showed that the differences in temperatures between the inside and outside of the office were 4.4°C, 3.8°C, 3.5°C and 2.9°C for silver film, blinds, tinted film and clear glass (5 mm), respectively. In terms of cost, the blinds proved to be low in cost with every temperature drop for temperature difference between internal and external temperatures. For every degree difference, silver coating would cost RM 6.80/°C, tinted laminating RM4.57/°C, blind RM 1.97/°C, and clean glass (5mm) RM 1.90/ °C . RM is Malaysian Ringgit and 1Euro= 4.50 RM. In addition the blinds could be easily fixed comparatively.